Autorzy:Podobińska Barbara, Przetacznik-Dąbrowa Teresa
Wydawnictwo:WSiP
Rok wydania:2013
Oblicz najprostszym sposobem. 2^(-1)*(0,1)^(-1)*(1/2)^(-1)4.45 gwiazdek na podstawie 11 opinii

Oblicz najprostszym sposobem. 2^(-1)*(0,1)^(-1)*(1/2)^(-1)

12Zadanie
14Zadanie
15Zadanie
1Zadanie
2Zadanie
3Zadanie
13Zadanie

a) `2^(-1)*(0,1)^(-1)*(1/2)^(-1)` `=(2*1/2*0,1)^-1=(0,1)^-1=10`

b) `(-1/3)^(-2)*(1/9)^(-2)*3^(-2)``=(-1/3*1/9*3)^-2=(-1/9)^-2= (-9)^2=81`

c) `(0,125)^(-3)*(-8)^(-3)*(1/2)^(-3)``=(0,125*(-8)*1/2)^-3=(-1/2)^-3=(-2)^3=-8`

d) `(-1,5)^(-4)*(-2/3)^(-4)*(0,1)^(-4)``=((-3/2)*(-2/3)*0,1)^-4=(0,1)^-4=10^4=10000`